III-V/Si staggered heterojunction based source-pocket engineered vertical TFETs for low power applications - Tripathy, Manas Ranjan; Singh, Ashish Kumar; Baral, Kamalaksha; Singh, Prince Kumar; Jit, Satyabrata (Superlattices and microstructures, 2020)
This article presents a comparative study on the performance characteristics of some vertical tunnel field effect transistor (TFET): conventional all-Si TFET with pocket, In0.53Ga0.47As/Si heterojunction TFET with pocket and GaSb/Si heterojunction TFET with pocket. Low band gap materials like In0.53Ga0.47As and GaSb are used here in source region of the TFETs which reduces the tunnel width to cause a greater number of carriers to tunnel through the source-channel heterojunction. Proposed III-V/Si heterojunction TFETs offer better sub-threshold swing, ION/IOFF ratio and lower threshold voltage over the conventional all-Si vertical TFET with pocket at VDS = 0.5 V. Along with the DC parameters, different analog/RF parameters are also extensively studied for all three TFET devices. In addition to this, effect of temperature on device DC performance is thoroughly investigated for the presented TFETs. Linearity parameters are also studied for all the three devices to assure better performance in a communication system at high-frequency. •This manuscript investigates the performance of III-V/Si staggered heterojunction based source-pocket engineered vertical TFETs.•The Low band gap material In0.53Ga0.47As and GaSb is used in the source region for the first time to enhance carrier tunneling.•The proposed V-TFETs with a pocket show improved sub-threshold swing (SS) below 40 mV/dec and ION/IOFF of the order 1011 at VDS = 0.5 V.•Maximum frequency of oscillation (fmax) is found to be as high as 800 GHz for the GaSb/Si proposed device.•Linearity parameters are studied for all the three proposed TFETs to assure better performance at high-frequency.